RELIGIOUS ATTITUDES AND VALUES PREFERENCES IN A SAMPLE OF YOUNG SPANISH UNIVERSITY STUDENTS - García Alandete, Joaquín; Pérez Delgado, Esteban (Anales de Psicología / Annals of Psychology, 2005)
One relevant question in Psychology of Religion is the relationship exists between religiosity and other personal variables of persons, like moral reasoning, values preferences and and others. In this report the goal is to inquiry the relationships betwenn religious attitude and values preferences in a group of youngs spanish university students (n= 323; 48 men, 275 women), using the Rokeach’s Values Scale (A) and a questionnaire of religious attitudes; we are interesting to inquiry if they are differential relations between hierarchy of values and religious attitudes. Hypothesis maintain that major and minor religiosity are associated differently to values preferences. Results obtained confirm the hypothesis, and it let to conclude that exist a significant relationship between some values.